Cytokines as biomarkers of Crimean-Congo hemorrhagic fever - Papa, Anna; Tsergouli, Katerina; Çağlayık, Dilek Yağcı; Bino, Silvia; Como, Najada; Uyar, Yavuz; Korukluoglu, Gulay (Journal of medical virology, 2016)
Crimean‐Congo hemorrhagic fever (CCHF) is a potentially severe disease caused by CCHF virus. As in other viral hemorrhagic fevers, it is considered that the course and outcome of the disease depend on the viral load and the balance among the immune response mediators, and that a fatal outcome is the result of a “cytokine storm.” The level of 27 cytokines was measured in serum samples taken from 29 patients during the acute phase of the disease. Two cases were fatal. Among survivors, significant differences between severe and non‐severe cases were observed in the levels of IP‐10, and MCP‐1, while the levels of IL‐1b, IL‐5, IL‐6, IL‐8, IL‐9, IL‐10, IL‐15, IP‐10, MCP‐1, TNF‐α, and RANTES differed significantly between fatal and non‐fatal cases (P < 0.05). RANTES was negatively correlated with the outcome of the disease. A striking similarity with the cytokine patterns seen in Ebola virus disease was observed. A weak Th1 immune response was seen. The viral load was positively correlated with IL‐10, IP‐10, and MCP‐1 levels, and negatively correlated with the ratio IL‐12/IL‐10. Especially IP‐10 and MCP‐1 were significantly associated with the viral load, the severity and outcome of the disease, and they could act as biomarkers and, probably, as potential targets for treatment strategies design. J. Med. Virol. 88:21–27, 2016. © 2015 Wiley Periodicals, Inc.